THE IMPACT OF CREDIT RISK ON THE FINANCIAL PERFORMANCE OF INDONESIAN STOCK EXCHANGE-LISTED BANKS - Verawati , Verawati; Sriwati , Sriwati; Kurniawati, Herni (Graduate Program of Universitas Tarumanagara, 2023)
The important role of banks as financial institutions tasked with collecting and distributing funds in the form of loans to the public aims at economic growth and the improvement of social welfare. In the big bank war, public trust is needed to save money in banks whose health is the top priority. To examine the health of your bank, you can use the Nonprofit Lending Ratio (NPL) analysis. The following applies. The lower the bad debt amount, the lower the credit risk borne by the bank and the better the financial performance of the bank. The purpose of this study is to empirically prove how the level of credit risk as measured by NPL ratio reduces or increases the financial performance of Bank Indonesia as measured by ROA and ROE. The study design is a descriptive quantitative approach. The study population includes all banking companies listed on the IDX for the period 2018-2021. The study sample used a sampling technique using a targeted sampling technique with a sample of 176 observations. This study uses panel data regression starting with model testing, classical assumption testing, and statistical testing. Statistical t-test results show that high bank credit risk can affect financial performance. Our contribution is for Management can work to raise the bank's health level by increasing third party funds (DPK), which will encourage clients to maintain their money in the institution, so raising the bank's health level to a healthy condition. Banks employ a variety of techniques, such as developing new innovations to boost customer security while also paying close attention to the issue of customer accessibility to raise customer pleasure, which in turn has an impact on boosting customer loyalty.